The assessment of the influence of training on functional parameters of the MTB cyclist/rider by means of laboratory test - Gabrys, T.; Szmatlan-Gabrys, U.; Ficek, K.; Mroz, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction. The aim of the research was to determine the parameters of an excercise test (Trial-MTB), allowing for the for the assessment of metabolism power and capacity over a single trial. The excersise had the following strata of intensity: oxygen regenerating (.LT), oxygen developing (>LT), oxygen-anaerobic (AT), anaerobic submaximal (>AT, LA = 6-8 mmol/l), and maximal (LA>9mmol/l), (Wilber R. et all.[1997). Material and methods The research was conducted during 12 weeks of special preparation period (February - April 2003) with the World Champion and V-Champion of the 2003 MTB Marathon. The Trial was based on the following factors: work time - 50% of the start work duration, AT and submaximal intensities dominant, recurring maximal intensity work and those below the AT threshold (simulating sharp uphill ride and easy downhill), test carried out on MTB, lab conditions. The excersise parameters were defined on the ground of the progressive trial (Hamilton L. et all. 2002. The progressive test and TRIAL-MTB were executed on a mobile track (Cosmos 2001, Germany). During the test the following data was recorded: VO2, VE, CO2 (V max 29 f. Sensormedic (USA), HR (Polar, Finland), LA (LP 20, LKM 140 Dr Lange, Germany). Also analyzed was the dynamics of physiological parameters and LA after two consecutive 6-week training sessions. Results. The stabilization of maxVO2 after the first mesocycle, the decrease after the second mesocycle (from 70 to 54.6 ml/kg/min) and similar characteristics of VO2 for the whole duration of the trial, regardless of the work intensity, indicate upsurge of oxygenic metabolism efficiency after the second mesocycle and increase of oxygenic conversions power after the first mesocycle. The decrease of HRmax (from 187 to 179 pulses/min) after the first mesocycle indicates adaptation of cardio-vascular system. The decrease of maximal myocardial contractions after mesocycle II indicates the growth of efficiency of the cardio-vascular system. The decrease of lactate concentration in blood (LA) after efforts on all levels of intensity after the first 6 week period indicates the increase of oxygenic metabolism power. The power required to perform the excercise is generated to a greater degree from the oxygenic metabolism energy; the work executed during the second 6 week period resulted in the stabilization of the oxygenic metabolism in the course of the excercise. The energy consumption cost was dramatically lowered in the case of submaximal intensity (LA down from 10.3 after the first 6 week period, to 5.71 and to 2.99 mmol/l after the second period) and the maximal one (LA down from 13.2 after I period to 5.92 mmol/l after II period), thus regarding the effort based on the energy procured from the anaerobic metabolism. Conclusions. The structure of the 60-minute specific laboratory excersise test TRIAL-MTB is comprised of efforts of the following intensity and total time elapsed: 21 minutes of LT intensity, 26 minutes of AT intensity, 10 minutes of submaximal intensity and 3 minutes of maximal intensity. The above structure allows for the definition of characteristic features of the adjustment processes in the period of special preparation training session of a MTB cyclist (rider).